IMPLEMENTASI PENERANGAN JALAN UMUM HIBRID ENERGI MATAHARI DAN ANGIN BERBASIS INTERNET OF THINGS - Murie Dwiyaniti; Silawardono; Nana Sutarna; Yani Haryani; Danang Widjajanto; Hasan Abdullah; Nabil Amanda; Randa Ahmad C.S, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Generally, streetlights installed on roads use solar power (PV) as an electricity source. However, PV is very dependent on sunlight and is limited. So streetlights based on PV require large-capacity batteries to be able to supply streetlights electricity for 12 hours (18.00-06.00). An alternative solution is to add other energy sources, for example, wind energy. This article discusses the implementation of streetlights that have two energy sources (hybrid PV and wind) with an IoT-based monitoring system. Various sensors are integrated to determine the performance of the PV-wind hybrid streetlights and data acquisition via the IoT platform in real-time for system analysis purposes. As a result, the PV-wind hybrid streetlights showed good performance. PV is capable of producing a voltage of up to 21.26 V. Meanwhile, a wind turbine is capable of producing a voltage of up to 13.97 V. The hybrid energy source of PV and wind synergizes well so that it can power streetlights 20% longer than streetlights based on PV alone. However, PV-wind hybrid streetlights are not optimal if implemented in the Depok area because the wind gust speed is very low. PV-wind hybrid streetlights are very suitable for implementation in areas with strong wind gusts such as coastal areas.